THE MATHEMATICAL DESCRIPTION OF PROCESS OF FORMATION OF GEOMETRICAL PARAMETERS OF THE SUPERFICIAL LAYER AND HARDENING AT PROCESSING DETAILS IN FRACTION - V.G. Lebedenko (Advanced Engineering Research, 2008)
The system of theoretical models past experimental check is developed. The given models can be used for increase of efficiency of strengthening processing in fraction at a stage of technological designing